Injury surveillance in an accident and emergency department: a year in the life of CHIRPP. Issue 6 (1st June 1999) - Morrison, A; Stone, D H; Doraiswamy, N; Ramsay, L
Abstract : BACKGROUND: The design of childhood injury prevention programmes is hindered by a dearth of valid and reliable information on injury frequency, cause, and outcome. A number of local injury surveillance systems have been developed to address this issue. One example is CHIRPP (Canadian Hospitals Injury Reporting and Prevention Program), which has been imported into the accident and emergency department at the Royal Hospital for Sick Children, Glasgow. This paper examines a year of CHIRPP data. METHODS: A CHIRPP questionnaire was completed for 7940 children presenting in 1996 to the accident and emergency department with an injury or poisoning. The first part of the questionnaire was completed by the parent or accompanying adult, the second part by the clinician. These data were computerised and analysed using SPSSPC for Windows. RESULTS: Injuries commonly occurred in the child's own home, particularly in children aged 0–4 years. These children commonly presented with bruising, ingestions, and foreign bodies. With increasing age, higher proportions of children presented with injuries occurring outside the home. These were most commonly fractures, sprains, strains, and inflammation/oedema. Seasonal variations were evident, with presentations peaking in the summer. CONCLUSIONS: There are several limitations to the current CHIRPP system in Glasgow: it is not population based, only injuries presented to the accident and emergency department are included, and injury severity is not recorded. Nevertheless, CHIRPP is a valuable source of information on patterns of childhood injury. It offers local professionals a comprehensive dataset that may be used to develop, implement, and evaluate child injury prevention activities.